The Effect of Transition Metal Doping on the Photooxidation Process of Titania-Clay Composites - Judit Ménesi; Renáta Kékesi; László Kőrösi; Volker Zöllmer; André Richardt; Imre Dékány (International Journal of Photoenergy)
Montmorillonite-TiO2 composites containing various transition metal ions (silver, copper, or nickel) were prepared, and their photocatalytic efficiencies were tested in the degradation of ethanol vapor at 70% relative humidity. Two light sources, UV-rich (𝜆 = 254 nm) and visible (𝜆 = 435 nm), were used. The kinetics of degradation was monitored by gas chromatography. It was established that, in the case of each catalyst, ethanol degradation was more efficient in UV-C (𝜆 = 254 nm) than in visible light, furthermore, these samples containing silver or copper ions were in each case about twice more efficient than P25 TiO2 (Degussa AG.) used as a reference. In photooxidation by visible light, TiO2/clay samples doped with silver or copper were also more efficient than the reference sample, P25 TiO2. We show that doping metal ions can also be delivered to the surface of the support by ion exchange and significantly alters the optical characteristics of the TiO2/clay composite.